A comparative study on different types of structures for onion storage - Yadav, SS; Yadav, VV (Vegetable Science, 2011)
Onion is one of the one of the most important vegetable crop of the country and plays a significant role in the routine diet of the people. A sizeable quantity of onion is exported from India mainly to gulf countries, Sri Lanka and south Asian countries. It is estimated that onion accounts for 87.5 per cent of annual export of vegetables from India (Roy and Chkrabarti, 1988). The rabi season crop yields 50- 60 per cent production whereas the kharif and late kharif season crop covers rest of the production. Generally, the harvested onion bulbs are stored in locally designed traditional structures all over the country, where 50 to 60 per cent losses incurred due to improper aeration (Pandita, 1994). Sometimes the entire produce is damaged so severely that it makes difficult to inhale in surrounding areas. Resultantly, farmers have no option to sale out their produces immediately after harvest at marginal rate.